(3NWhI YRjRI(B!s - (3YHO GdQMje, CMeOs; (3CHh ZfjeI, fHjds ((3HjQhJs (3OGQ CUGdIs, 2020)
(3SeYJ (B"(3beQ(B" (3Yf (B"(3YRjRI(B" (3GdVNeI GdJj jNGa efgG CgGdj GdbQjI(B... (3Edi Cf hLOJ (B"(3beQ(B" (3faSgG CeGegG hLgG dhLg, aeGPG jMOK HjfgeG?(B!s
(3GdehVhY (B: (3GdGNJdGa, JbHd GddBNQ, GdeSGYOI, GdTLGYIs
(3bUU YQHjIs
Keywords: (3GdbUU GdYQHjI GdbUjQIs -- (3dHfGfs